Pengembangan Trafo Distribusi Berdasarkan Pertumbuhan Beban Tahun 2012 – 2016 di UPJ Batang - Mahardhika, Dhimas; Nugroho, Agung; Sukmadi, Tejo (Transmisi, 2010)
Electric energy infrastructure as one of the livelihood of the people concerning the distribution of electrical energy must be able to guarantee in an amount sufficient, reasonable price and good quality. Electrical energy demand will increase in line with regional economic development and population growth and the growth of electric power loads. And It need forecasting electrical energy within a period of 5 years and doing physical development. One of them, ​​the development of distribution transformers to help electrical service to the new customers. In meeting the increasing electricity, then implemented the development of distribution networks. In the development of distribution networks, it would require the development of distribution transformers. In the development of distribution transformers, electricity demand forecasting needs to be done to get the load growth. Forecasting model used is using the DKL 3.2 model. After getting the results of load growth (KVA) with DKL 3,2 model, then divided according to the needs of growth so that the load can be simulated to ETAP 7.0.0 software simulates previously existing in 2011 as the basis of the development of distribution transformers in 2012 to 2016 from result study in PT PLN Persero UPJ Batang. From the calculation of the development of distribution transformers based on load growth forecasting results DKL model 3.2, it was found that the number of placements the development of distribution transformers based on land-use map of the area which is then divided in accordance with the development of the existing load growth. Showed that the number and type distribution transformers capacity development each year is different. From 2012 to 2016, there were variations in the number and type of capacity transformer including transformer 1 phase 50 KVA, 3 phase 50 and 100 KVA, and also the replacement transformer or upgrading of transformer 1 phase 25 to 50 KVA. After simulated using ETAP 7.0.0, the losses of energy development in 2012 to 2016 has increased gradually due to the load growth. But there are some feeders whose load to be cut, so that the losses value of energy to be down. Keyword :   Diistribution of electric energy, Load forecasting, DKL 3.2, ETAP 7.0.0, Development of distribution transformers